Child feeding practices and male involvement in child feeding among smallholder farming households in Uganda - Nabuuma, Deborah; Ekesa, Beatrice (Süleyman Demirel University, 2024)
Smallholder farmers continue to face food and nutrition insecurity. The timing, scope and effectiveness of interventions is influenced by decision-making and roles within households and communities, yet emphasis has majorly been placed on mothers. A cross-sectional study explored the child feeding practices and extent of the father’s participation in child feeding among 433 farming households with children aged 6-35 months from two rural and two peri-urban districts in Central Uganda. Diets consumed by children were inadequate with only 37% meeting the minimum dietary diversity. About 65% of fathers participated in decision-making over child feeding with 10% all the time and 24% only a few times. Additionally, 48% of fathers participated in actual child feeding, 2% all the time and 23% only a few times. Main reasons for the level of father participation included the presence or absence of money or food; concern or lack of concern over the child’s health; father’s physical availability; and whether child feeding is part of a father’s responsibility or not. Fathers who participated in decision-making regarding child feeding were more likely to participate in actual child feeding (r=0.6, P<0.01). There is an opportunity for active engagement of fathers in nutrition-related interventions to enhance their participation and support in decisions concerning child feeding and actual child feeding for enhanced child and household food and nutrition security.